Surface ionization state and nanoscale chemical composition of UV-irradiated poly(dimethylsiloxane) probed by chemical force microscopy, force titration, and electrokinetic measurements - Song, Jing (Langmuir : the ACS journal of surfaces and colloids, 2007)
The surface chemistry and ionization state of cross-linked poly(dimethylsiloxane) (PDMS) exposed to UV/ozone were studied as a function of treatment time. Various complementary and independent experimental techniques were utilized, which yielded information on the macroscopic as well as the nanometric scale. The average chemical composition of the PDMS surface was quantitatively investigated by time-of-flight secondary ion mass spectrometry (ToF-SIMS). It was found that the top 1-2 nm surface layer was dominated by silanol groups (-SiOH) for which the concentration increased with increasing treatment dose. The lateral distributions of the silanol groups were analyzed on the nanometer scale by means of atomic force microscopy (AFM) with chemically functionalized tip probes in aqueous buffer solutions at varying pHs. Spatially dependent pull-off force curves (also called "force volume" imaging) indicated the presence of strong chemical heterogeneity of the probed surface. This heterogeneity took the form of patches of silanol functionalities with high local concentration surrounded by a matrix of predominantly hydrophobic domains at low pH. The average pull-off forces for the entire surface scanned were significantly reduced for pH values larger than a characteristic pK(a) constant (in the range between 4.5 and 5.5). The extent of the decrease in the pull-off force and the particular value of pK(a) were found to be a function of treatment time and to differ from the commonly reported values for silanol functional groups on a homogeneous silica surface. These dependences were ascribed to the evoking of a protonation/deprotonation process of the surface silanol groups which was sensitive to the hydrophobic/hydrophilic balance of their close molecular environment. Intermolecular hydrogen bonding may also account for the shifts in the surface pK(a). Furthermore, depending on the nature of the electrolyte, a third effect related to double layer composition, as determined by specific ion adsorption, was quantitatively analyzed by streaming potential measurements in the presence of sodium chloride and phosphate electrolytes